ECCENTRIC Buildings: Evaporative Cooling in Constructed ENvelopes by Transmission and Retention Inside Casings of Buildings. (November 2015) - Teitelbaum, Eric; Meggers, Forrest; Scherer, George; Ramamurthy, Prathap; Wang, Louis; Bou-Zeid, Elie
Abstract: New research on evaporative cooling and breathable walls has demonstrated the potential for smart designs where conductive, convective, and radiative heat fluxes are matched or supplemented through low-energy natural phenomena such as wet-bulb temperature depression associated with evaporation. This research seeks to examine the operational and theoretical performance of novel vapor permeable evaporative cooling membrane layers. Latent heat is removed through the evaporation of water through the membrane, where contaminants remain in solution as the hydrophobic membrane allows for passage of only water vapor. Through steady-state analysis of a proposed cooling system for building exterior walls, cooling capacity was shown to exceed cooling loads for large indoor areas. Candidate materials produced from recycled glass were examined through sintering, hydrophobing, and other processes to create materials with the requisite properties specified by simulations. Real data acquired for Princeton, NJ from July 2011 was inputted to the simulations to quantify behavior of the system under real conditions. Even in the humid climate of New Jersey in July, the system can supplement a conventional cooling system, acting as a buffer between interior and external environments. Additionally, the novel mathematical model developed to simulate this evaporative process is in 0.04 ± 0.28 °C agreement to measured data.